2020
DOI: 10.1111/mec.15493
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhizal fungal diversity decreases in Mediterranean pine forests adapted to recurrent fires

Abstract: Fire is a major disturbance linked to the evolutionary history and climate of Mediterranean ecosystems, where the vegetation has evolved fire‐adaptive traits (e.g., serotiny in pines). In Mediterranean forests, mutualistic feedbacks between trees and ectomycorrhizal (ECM) fungi, essential for ecosystem dynamics, might be shaped by recurrent fires. We tested how the structure and function of ECM fungal communities of Pinus pinaster and Pinus halepensis vary among populations subjected to high and low fire recur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 103 publications
(171 reference statements)
0
13
0
Order By: Relevance
“…Other processes like dispersal limitation or stochastic processes such as niche pre-emption (i.e. priority effects, Kennedy et al, 2009) might have a secondary role, potentially due to continuous forest cover promoting inoculum arrival from nearby similar forests (Redondo et al, 2020), but still mainly shaping ectomycorrhizal compositional patterns at regional spatial scales. The geographical distance effect on the soil fungal communities observed here is in accordance with distance decay similarity patterns observed in different ecosystems at local and regional scales (e.g.…”
Section: Fungal Communities Determined By Geographical Distance and Soil Rather Than Forest Structurementioning
confidence: 99%
“…Other processes like dispersal limitation or stochastic processes such as niche pre-emption (i.e. priority effects, Kennedy et al, 2009) might have a secondary role, potentially due to continuous forest cover promoting inoculum arrival from nearby similar forests (Redondo et al, 2020), but still mainly shaping ectomycorrhizal compositional patterns at regional spatial scales. The geographical distance effect on the soil fungal communities observed here is in accordance with distance decay similarity patterns observed in different ecosystems at local and regional scales (e.g.…”
Section: Fungal Communities Determined By Geographical Distance and Soil Rather Than Forest Structurementioning
confidence: 99%
“…An indicator species analysis (ISA) was conducted with the "indicspecies" package for R in order to identify indicator taxa characteristic of the bacterial and fungal communities (Pérez-Izquierdo et al, 2020;Rodríguez-Caballero et al, 2017). The relative abundances of microbial families and OTUs in each sample were used to calculate the Indicator Value (IndVal) and its significance.…”
Section: Discussionmentioning
confidence: 99%
“…After a fire, the recolonization is pioneered by spore-formers or fast-growth strategies microorganisms adapted to the high release of nutrients of a post-fire environment, principally oxidizable carbon and inorganic nitrogen (Bárcenas-Moreno et al, 2011;Choromanska and DeLuca, 2002;Goberna et al, 2012). This fact might be related to the high dominance of Actinobacteria and Firmicutes bacteria phyla and Ascomycota and Basidiomycota fungi phyla in the soils unaltered by SL (C), all described as positively influenced by fire disturbances (Ferrenberg et al, 2013;Pérez-Izquierdo et al, 2020;Prendergast-Miller et al, 2017). Moreover, the mosaic of soil patches, that offer the burned wood distribution, provides a variety of carbon substrates that promote specialization strategies (Goldfarb et al, 2011;Miller and Chesson, 2009), and simultaneously softens microclimatic conditions facilitating microbial development (Marañón-Jiménez et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Drought can also interact with fires, as shown experimentally on a Cistus‐Erica system where microbial activity after fire was reduced by drought (Hinojosa et al, 2016). The study of the interactions among stressors (fire, drought, etc), plant and microbial communities now benefits from the output of up‐to‐date environmental genomics approaches (e.g., Pérez‐Izquierdo et al, 2020).…”
Section: Adaptive Potential Of Exemplary Mediterranean Ecosystemsmentioning
confidence: 99%
“…Regarding fires, experimental approaches have shown that it can importantly modify the bacterial composition of the soil with an effect depending on fire intensity (Lucas‐Borja et al, 2019). A study on pine forests ( Pinus halepensis and P. pinaster ) has shown that recurrent fires can also modify the fungal communities, with a lower diversity of ectomycorrhizal species (Pérez‐Izquierdo et al, 2020). Drought can also interact with fires, as shown experimentally on a Cistus‐Erica system where microbial activity after fire was reduced by drought (Hinojosa et al, 2016).…”
Section: Adaptive Potential Of Exemplary Mediterranean Ecosystemsmentioning
confidence: 99%